Sufficient conditions for the Inversion Formula for the k-plane Radon Transform in R^n - Jensen, Sine R. (Mathematica Scandinavica, 2004)
The inversion theorem (1) for the k-plane Radon transform in R^n is often stated for Schwartz functions, and lately for smooth functions on R^n fulfilling that f(x)=O(|x|^-N) for some N>n, cf. [6]. In this paper it will be shown, that it suffices to require that f is locally Hölder continuous and f(x)=O(|x|^-N) for some N>k (N not necessarily an integer) in order for (1) to hold, and that the same decay on f but f only continuous implies an inversion formula only slightly weaker than (1).